TRACE OF MARITIME CULTURE AND TRADE OF THE MAJAPAHIT KINGDOM - Anita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The problem in this research is how the hegemony of the Majapahit kingdom was and how trade was during the Majapahit kingdom, with the aim of the research being to find out the hegemony and trade of the Majapahit kingdom. The research method used is the library study research method, which means collecting information that is relevant to the topic or problem that is the object of research. The research results show that the Majapahit kingdom was the largest Hindu-Buddhist kingdom in Indonesia which was founded by Raden Wijaya in 1293-1527 in the 13th to 16th centuries. During the Majapahit kingdom, trade was not carried out freely. To regulate the rhythm of trade, along with taxes, in the royal bureaucracy there was a rakryan kanuruhan or